Dinâmica ictioplanctônica em ambientes hipersalinos do semiárido brasileiro - Badú, Maria Luísa de Araújo Souto (2019)
Estuaries are habitats often considered as “nursery areas” as they provide a wide range of resources that favor the development of many organisms primarily in their early stages, considered a critical period in life cycle of these species.The structural particularities as well as the fluctuations of hydrological cycle in these environments provoke seasonal and spatial variations in environmental parameters determinant in distribution and structure of fish community. Thus, the study arose with the purpose of describing the structure and spatio-temporal distribution of ichthyoplankton in two hypersaline estuaries (Tubarão and Casqueira river estuaries) of municipality of Macau - RN, Brazil. The estuaries were divided into three zones according to their saline gradients where they were sampled in 2017 and 2018 covering periods of drought and rain of the region. With aid of a conical - cylindrical plankton network, horizontal subsurface trawls were made and environmental parameters checked at high tides. The larval species that most contributed to density values were Atherinella brasiliensis, Lile piquitinga, Oligoplites saurus and Caranx latus, while the Engraulidae and Clupeidae families were the most representative egg families. The variables that best predicted the ichthyoplankton variation were rainfall, depth, temperature and channel width at sampling site. The highest ichthyoplankton densities were observed in intermediate zone of the Tubarão estuary during the dry period. The density of larvae presented significant difference only between periods and estuaries while eggs presented differences of densities between estuaries, zones and periods. And the larval development pointed a separation in the development of larvae relating lower developmental stages (vitellin and pre-flexion) with dry period and higher developmental stages (flexion and post-flexion) with the rainy season in both estuaries. The results evidenced high sensitivity of ichthyoplankton to environmental variations, emphasizing its role as a tool for the evaluation of effects of environmental changes, and presence of typically marine dependent estuarine species confirm the importance of these estuarine environments as nursery areas, even under conditions of hypersalinity.